Pengaruh Kompensasi Terhadap Kinerja Dosen Non-PNS Dalam Melaksanakan Pendidikan Dan Pengajaran di Prodi PIAUD FITK UIN Raden Fatah Palembang - Murtopo, Ali; Cindrya, Elsa (El-Idare: Journal of Islamic Education Management, 2021)
Researchers conducted research at UIN Raden Fatah, especially in the Early Childhood Islamic Education Study Program, which is located at Jalan Professor K.H Zainal Abidin Fikri Km. 3,5 Palembang, 2nd floor multimedia building. Time The study was conducted from April to August 2020. The results of research at PIAUD FITK UIN Raden Fatah Palembang indicate that the compensation variable used is valid, which is seen from the Corrected Item-Total Correlation and is significant on lecturer performance. In accordance with the t test. The results of the research on the PIAUD FITK PROGRAM at UIN Raden Fatah Palembang show that the compensation at the PIAUD FITK PRIVATE VOCATIONAL SCHOOL, UIN Raden Fatah Palembang has a significant and significant influence on the performance of non-PNS permanent lecturers. In accordance with the t test with a t- count value of 0.30 while the t-table value with a significant level of 0.05 is 0.461. So that the comparison is tcount <ttable (0.461 <3.182), then Ha is accepted, which means that the compensation variable has a significant effect on the performance of non-PNS permanent lecturers at PIAUD UIN Raden Fatah Palembang.